Subchronic toxicity study in BALBc mice of enterocin AS-48, an anti-microbial peptide produced by Enterococcus faecalis UGRA10. (October 2019) - Baños, Alberto; García, J. David; Núñez, Cristina; Mut-Salud, Nuria; Ananou, Samir; Martínez-Bueno, Manuel; Maqueda, Mercedes; Valdivia, Eva
Abstract: Few studies have examined the use of animal models to evaluate the in-vivo toxicity of antimicrobial peptides, but such research is essential to their safe use in foods. This study was performed to evaluate any adverse effects of enterocin AS-48, a circular bacteriocin produced by Enterococcus strains, when administered to BALB/c mice at concentrations of 50, 100, and 200 mg/kg in the diet for 90 days. Animals dosed with nisin at a dietary concentration of 200 mg/kg served as a reference treated group. There were no deaths in any of the animal groups, and the AS-48 treatment produced no abnormalities or clinical signs on body weights, food consumption, urinalysis, haematology, or blood biochemistry. Furthermore, there were no significant differences in the weights of liver, spleen, heart, kidneys, and intestines between control mice and those treated with AS-48 or nisin. The histopathological study showed moderate vacuolar degeneration in hepatocytes of some animals fed 100 or 200 mg/kg AS-48 (3/10 and 2/10 respectively). However, this anomaly was lower than in the group treated with nisin (5/10). Conclusively, no toxicologically significant changes were associated in BALB/c mice fed with 50, 100, and 200 mg/kg enterocin AS-48 for 90 days. Highlights: The subcronic toxicity of enterocin AS-48 has been assayed in mice. AS-48-treated mice did not show abnormalities in body weight or food consumption. AS-48 diet did not alter urine, haematology or blood biochemistry parameters. AS-48 did not alter liver, spleen, heart, kidneys and intestines weight or histology. Hepatocytes of AS-48-treated mice showed moderate vacuolar degeneration.